The Lean Leader - Camp, Robert (Ascent Audio, 2019)
The Lean Leader: A Personal Journey of Transformation uses a compelling novel format to tackle the nuts and bolts of leading a Lean transformation. Listeners follow along as the characters face real crises and what seem to be unreasonable deadlines. As the story progresses, listeners will see how the main character, Don, and his colleagues transform from being "command and control" autocrats-those who make decisions and bark orders-to more Socratic coaches and mentors. As Don and his staff come to realize that the folks they employ are the real experts in the processes they control, you will learn why it behooves you to do more asking than telling. You will come to realize that a leader's greatest skill must be in coaching great performance from their people. You will also witness the difference between managing and leading. After finishing this book, you will understand why it's so important to shed the decision-making tasks that have cluttered your days, and how to delegate those decisions to employees who are closer to the action. You will learn how important it is to look over the horizon to identify upcoming challenges, define and communicate new courses of action, and compel others to follow. Most importantly, you will learn exactly what it takes to lead a Lean organization that thrives socially, as well as financially.